Quechua languages in three Andean-Amazonian countries: from census data to citizen action - Andrade Ciudad, Luis (2021)
This article examines various aspects of the current situation of the Quechua languages in three Andean-Amazonian countries: Ecuador, Peru, and Bolivia. After studying the most recent census data and the regional distribution of this linguistic family in these three countries, the authors discuss the social use of Quechua and Quichua and describe some of the changes that have taken place in this field in recent years. There is still a long and difficult way to go –in some countries more than in others– for Quechua-speaking people’s language rights to be respected, we present various legal, political, and citizen action initiatives that, in recent years, have been opening up potential pathways to this end.